Direct uptake of soil nitrogen by mosses - Ayres, Edward; Van Der Wal, René; Sommerkorn, Martin; Bardgett, Richard D. (Biology Letters, 2006)
Mosses are one of the most diverse and widespread groups of plants and often form the dominant vegetation in montane, boreal and arctic ecosystems. However, unlike higher plants, mosses lack developed root and vascular systems, which is thought to limit their access to soil nutrients. Here, we test the ability of two physiologically and taxonomically distinct moss species to take up soil- and wet deposition-derived nitrogen (N) in natural intact turfs using stable isotopic techniques (15N). Both species exhibited increased concentrations of shoot 15N when exposed to either soil- or wet deposition-derived 15N, demonstrating conclusively and for the first time, that mosses derive N from the soil. Given the broad physiological and taxonomic differences between these moss species, we suggest soil N uptake may be common among mosses, although further studies are required to test this prediction. Soil N uptake by moss species may allow them to compete for soil N in a wide range of ecosystems. Moreover, since many terrestrial ecosystems are N limited, soil N uptake by mosses may have implications for plant community structure and nutrient cycling. Finally, soil N uptake may place some moss species at greater risk from N pollution than previously appreciated. © 2006 The Royal Society.